Ascorbic acid prevents N-nitrosodiethylamine-induced hepatic injury and hepatocarcinogenesis in Akr1a-knockout mice. (15th October 2020) - Ishii, Naoki; Homma, Takujiro; Guo, Xin; Yamada, Ken-ichi; Yamada, Sohsuke; Fujii, Junichi
Highlights: An ascorbic acid deficiency aggravates hepatic damage by N -nitrosodiethylamine (NDEA). Ascorbic acid supplementation increased reserves in the liver in response to NDEA treatment. Ascorbic acid copes with the hepatotoxic action of NDEA via multiple processes. Abstract: To gain insights into the benefits of ascorbic acid (AsA) in hepatoprotection, we examined the status of Akr1a −/− (KO) mice, which biosynthesize AsA at about 10% the rate as Akr1a +/+ (WT) mice, in terms of their response to an N -nitrosodiethylamine (NDEA)-induced hepatic injury. The intraperitoneal injection of NDEA (35 mg/kg) started at 4 weeks of age and was performed at weekly intervals thereafter. While the fatality rate was substantial in the KO mice, AsA supplementation (1.5 mg/ml in the drinking water) greatly extended their life-spans. Only two out of 54 KO mice survived to 28 weeks, and both contained approximately an order of magnitude greater number of tumor nodules compared to WT mice or KO mice with AsA supplementation. Histological and biochemical examinations at 20 weeks indicated that AsA potently protected against the hepatotoxic action of NDEA. Interestingly, the AsA levels in the liver were higher in the AsA-supplemented KO mouse groups that had received the NDEA treatment compared to the corresponding control group. While the protein levels of Cyp2e1, an enzyme that plays a major role in the bioactivation of NDEA, had declined to a similar extent among the experimental groups, p -nitrophenol-oxidizing activity was sustained at high levels in the KO mouse livers but AsA supplementation suppressed this activity. These findings confirm that AsA is a potent micronutrient that copes with hepatic injury and cancer development caused by exposure to NDEA in the livers of Akr1a-knockout mice.